THE USE OF ROLE PLAY METHOD TO IMPROVE STUDENT COMPREHENSION IN READING NARRATIVE TEXT AT - LIAVANY SITANGGANG; MEI KRISTINA SINAGA; YUNIKA P S SEMBIRING; HARSELLA SEMBIRING (CV KULTURA DIGITAL MEDIA, 2022)
Learning is an activity with an intention so that the learning process of a person or group of people can take place. For this reason, a teacher must strive to create a conducive environment or condition system so that learning activities can achieve goals effectively and efficiently (Sunaryo, 1996: 16). Reading is one part of skill in english that should be learn. Reading is one of English skill that should be mastered by the foreign learner in Indonesia, especially the students in Junior High School. The aim of this research was to know whether or not the use of role play technique could improve the IX-A grade students’ comprehension in reading narrative text at SMPN 1 Pematangsiantar. The research design used was Classroom Action Research. The data of this research was taken from test,interview, and observation. The result showed some improvements in each cycle. In Cycle 1, there were about 13 students who were active in teaching learning activity. In Cycle 2, there was 19 students who were active in teaching learning activity. It indicated that the use of Role Play technique could improve the students’ comprehension in reading narrative texts at the nine grade of SMP N 1 Pematangsiantar.